Bibliometric analysis and visualization of the research on the relationship between RNA methylation and immune cell infiltration in tumors - Meng, Sibo; Yang, Guanghui; Yu, Enhao; Li, Jiaxin (Frontiers in Immunology, 2024)
BackgroundThis research endeavors to delve into the research hotspots and trends concerning RNA methylation and tumor immune cells through the application of bibliometric analysis and visualization techniques.MethodsA comprehensive search in WoSCC (2014-2023) for RNA methylation and tumor immune cell articles/reviews was conducted. Bibliometric analysis and visualization employed CiteSpace, Bibliometric, and VOSviewer tools.ResultsA total of 3295 articles were included in the analysis, with a continuously increasing number of publications linking RNA methylation to tumoral immune cells. Chinese authors and research institutions have demonstrated a sustained growth trend in both the number of publications and author influence. SUN YAT SEN UNIVERSITY, a Chinese institution, has published the highest number of articles in this field, while also demonstrating extensive international and inter-institutional collaborations. Meanwhile, HARVARD UNIVERSITY has also achieved impressive results. For instance, Frontiers in Immunology has published the largest number of articles in this category. Nature Communications has published articles that are most influential in this field, playing a pivotal role in disseminating research findings. The sustained vitality of this field is attributed to its solid research foundation, including the groundbreaking work published by Professor Chiappinelli KB in Cell and the widely cited paper by Professor Han DL in Nature. Analysis of research trend topics reveals that m5C, immunotherapy, and the immune microenvironment are current research focuses.ConclusionFuture investigative efforts at the juncture of RNA methylation and tumor immune cells are anticipated to concentrate on domains including m5C, n7-methylguanosine, cuproptosis, prognosis assessment, immunotherapeutic strategies, and the tumor microenvironment.